Digital Shadows: A Study of Cyber Incursions and Human Rights Breaches - Tyagi, Richa (Trinity Law Review, 2024)
The progress of any society depends upon the fact that how their rights are protected  and nourished. In the era of digital transformation where ICT is becoming a  dominant factor for governing the individuals action the need to protect the basic  rights of the individuals becomes a prime important objective of this generation.  The intrusions in the cyberspace have not only challenged the integrity of public  authorities or the private organization but have deeply impacted the realization  of human rights at the individual level. The article is an attempt to bring forth  the concept of cyber-crimes, the motives which lead to the manifestation of  cybercrimes against individuals and the human rights which are violated by these  forms.
Keywords: Information and Communication Technology (ICT); Cybercrimes; Cybercriminals; Cyber stalking; Cyber-bullying; UDHR